2001
DOI: 10.3349/ymj.2001.42.2.247
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of 4,514 cases of renal biopsy in Korea

Abstract: To evaluate the distribution and changing patterns of renal diseases in Korea, a total of 4,514 cases of renal biopsy collected over a 23-year period between 1973 and 1995 were reviewed. Of 4,200 cases excluding 314 unsatisfactory biopsies, adult cases comprised 59.5% and pediatric cases, 40.5%. The male to female ratio was 1.5:1 in adults and 2.2:1 in children. Glomerulonephritis (GN) comprised 80.0% of the total. The most common primary GN in adults was minimal change disease (MCD) (26.6%), followed by IgA n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
63
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 0 publications
15
63
3
1
Order By: Relevance
“…In patients with NS the most common diagnosis was FSGS (20.2%), followed by MGN (18.8%). In most other studies it was reversed, MGN was the most common, followed by FSGS [2,3,7,10]. This could be result of our relative liberal biopsy policy, including more patients with AUA, a more likely presentation of FSGS than MGN.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…In patients with NS the most common diagnosis was FSGS (20.2%), followed by MGN (18.8%). In most other studies it was reversed, MGN was the most common, followed by FSGS [2,3,7,10]. This could be result of our relative liberal biopsy policy, including more patients with AUA, a more likely presentation of FSGS than MGN.…”
Section: Resultsmentioning
confidence: 82%
“…We routinely use IF and electron microscopy in the renal biopsy analysis in all our patients, and we believe that this is one of the major advantages of our study. Consequently, there is a much bigger prevalence of HERNEF (8.1%) in our study compared to some others [5,10,11,[14][15][16]18]. Recent articles showed that electron microscopy was absolutely necessary to make a correct diagnosis in 21% of cases, while its use resulted in clinically relevant refinement of or addition to the diagnosis in another 24% of cases [31,32].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Also in India, a study conducted to identify the spectrum of renal diseases in Indian adults (Agarwal SK, Dash) 6 revealed that among the nephrotic syndrome cases primary glomerulonephritides was seen in 58.5% cases and of which minimal change disease (MCD) was the commonest cause in 38% of cases. In our study, more than 85% cases had primary glomerulonephritides amongst which 34% had MGN, FSGS in 25% and MCD in 20%.Studies by Dragovic et al 7 and Braden GL et al 8 found that FSGS was increasing in incidence in both white as well as black patients. Regarding the outcome of the different glomerular diseases, FSGS had a fairly high progression rate to end-stage renal disease (ESRD) among primary glomerular disease, while diabetes had a high incidence of ESRD among secondary glomerular disease.…”
Section: Discussionmentioning
confidence: 63%
“…38 Most of the studies did not mention IgM nephropathy as a distinct category. 13 We did not get any IgA nephropathy in our study.…”
Section: Primary Gnmentioning
confidence: 99%